Return-to-play testing and functional assessment following upper extremity injury in athletes: a systematic literature review - Mario Febrian; Andre Igoresky; Ifdil Ifdil (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
One of the toughest challenges in sports medicine is figuring out when an athlete can safely return to play after an upper extremity injury. Functional performance tests, isokinetic strength assessments, and patient-reported outcome measures are commonly used, but there is still no widely accepted, evidence-based RTP framework for shoulder, elbow, or wrist injuries. This systematic review pulled together the latest evidence on RTP assessment, pinpointed criteria backed by research, evaluated the tools available, and pointed out where studies are still lacking. The review followed PRISMA 2020 guidelines and searched the Scopus database for English-language studies published between 2021 and 2026. Two independent reviewers handled study selection and data extraction, with strong agreement (Cohen's κ = 0.87). Methodological quality was checked using the Joanna Briggs Institute checklist. Out of 633 records, only 10 studies made the cut. Four main themes came out of the analysis. First, criteria-based RTP protocols led to fewer reinjuries compared with time-based clearance, even when some functional deficits remained. Second, isokinetic rotational strength and limb symmetry turned out to be the strongest predictors of successful RTP. Third, functional tests like the Closed Kinetic Chain Upper Extremity Stability Test and Unilateral Seated Shot-Put Test showed real clinical value, but they need population-specific normative data to be more useful. Fourth, psychological readiness played its own role in RTP decisions, independent of physical measures. Wearable sensors and artificial intelligence show potential for continuous monitoring, but stronger prospective evidence is still needed. Overall, the current evidence supports a multidimensional RTP framework that combines objective strength, functional performance, and psychological readiness. At the same time, it highlights the need for standardized, pathology-specific criteria through future multicenter prospective studies.